2011
DOI: 10.1002/ange.201103745
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Scale Edge Structures on Industrial‐Style MoS2 Nanocatalysts

Abstract: Atome am Rande: Die atomaren Kanten des industriellen MoS2‐Nanokatalysators wurden durch einzelatomempfindliche Transmissionselektronenmikroskopie abgebildet (siehe Bild). Die beobachteten Kantenabschlüsse stimmen mit Voraussagen aus Modellstudien überein, und die Ergebnisse tragen dazu bei, die „Materiallücke“ in der Katalyse zu schließen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 35 publications
2
56
0
Order By: Relevance
“…3a, b). Although the edge structure is difficult to be determined conclusively, there is evidently strong preference for zig-zag edge orientation, consistent with theoretical predictions 38,39 and experimentally observed structures, [39][40][41][42][43] suggesting that 50% S and 100% S saturated zigzag molybdenum-edges should be thermodynamically preferred. [43][44][45] The HRTEM images also show the presence of material at the edges, which may correspond to carbonaceous species.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…3a, b). Although the edge structure is difficult to be determined conclusively, there is evidently strong preference for zig-zag edge orientation, consistent with theoretical predictions 38,39 and experimentally observed structures, [39][40][41][42][43] suggesting that 50% S and 100% S saturated zigzag molybdenum-edges should be thermodynamically preferred. [43][44][45] The HRTEM images also show the presence of material at the edges, which may correspond to carbonaceous species.…”
Section: Discussionsupporting
confidence: 80%
“…4f), with the 50% S edge more stable over a wide range of S chemical potential. [40][41][42][43][44] These edges have been both observed experimentally and it has been shown that the edge configuration depends on the synthesis conditions. [40][41][42][43] Although further studies need to be done in order to fully unveil the processes occurring at these edges, some theoretical studies have already shown the possibility of their modification through adsorption and desorption processes.…”
Section: Discussionmentioning
confidence: 85%
“…We also observed other point or line defects, but with much lower density. Great care was taken in TEM experiments to prevent knock-on damage or lattice reconstruction caused by 80 keV electron beam irradiation 28,29 . To rule out the effect of electron irradiation on vacancy density, we studied the evolution of defects under different exposure time.…”
Section: Resultsmentioning
confidence: 99%
“…S12). It is noteworthy that long-time electron irradiation at 80 kV could generate SVs due to knock-on damage 28,29 . Therefore, after we moved to an area, we limited the exposure time to o30 s (to adjust focus) before imaging.…”
Section: Methodsmentioning
confidence: 99%
“…For each individual layer, MoS 2 prefers to expose two types of low index edge terminations: the (1010) S edge and the (1010) Mo edge, as shown in Figure 1b [33,40,41]. When the size becomes smaller, like the MoS 2 cluster synthesized on Au (111), a triangular shape feature can be observed (Figure 1c) [33].…”
Section: Edge Structures Of Mosmentioning
confidence: 97%